Veterinary antimicrobial card game improves antimicrobial selection skills in veterinary students - Wolf, Jacob; Berger, Ashton C.; Colon, Elayne P. (Frontiers in Veterinary Science, 2025)
IntroductionThe inclusion of active learning in veterinary medical education has received significant focus in recent years. Game-based learning is an unconventional form of active learning and its use in education within the health sciences has been investigated.MethodsThis study evaluated the use of a card game to teach antimicrobial use in dogs and cats with bacterial diseases as a supplement to traditional methods of teaching.ResultsThis study found that third- and fourth-year veterinary students’ comfort in antimicrobial decision-making increased for four infectious diseases following the inclusion of a card game during rounds. No similar improvement was noted for a disease that was not included in the card game. Students perceived that the game improved their understanding of antimicrobials in dogs and cats and students universally enjoyed playing the game.DiscussionThe role of games in veterinary medical education should be further explored, especially studies that evaluate knowledge retention throughout the duration of their educational experience.